Israel : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper examines labor productivity in Israel. Israel's GDP per capita is low relative to the United States despite high labor input, as labor productivity is low. Catch-up of labor productivity to the United States stopped in the 1980s and relative labor productivity has since declined. Low labor productivity is the result of a low capital-to-labor ratio-kept low by high employment growth-and low total factor productivity growth. The latter may reflect lack of competition and product market restrictions, which are among the highest in advanced economies. Boosting competition, lowering product-market restrictions, and improving the quality of education and infrastructure would help boost productivity.